SISTEM PAKAR KESEHATAN PADA IBU HAMIL BERBASIS MOBILE WEBSITE - Setiyani, Umi; Subari, Arkhan (Gema Teknologi, 2015)
Umi Setiyani, Arkhan Subari, in this paper explain that the maternal mortality rate in Indonesia is still high, every 1 hour, 2 maternal death. Lack of information about the health of pregnant women, to be one cause. By utilizing the WAP ( Wireless Application Protocol ) and expert systems can be made to maternal health expert system -based mobile website. Maternal health expert system is able to diagnose 15 to 61 illnesses symptoms often suffered by pregnant women . Diagnosis of the disease is designed using forward chaining inference engine with the aid of decision tables and decision trees . In addition the system is also able to calculate the daily calories needed by pregnant women using cooper . So with this system can help pregnant mothers to know their health condition .Â Keywords : expert system , Wireless Application Protocol , the health of pregnant women.ReferencesNatalia, Deasy Astrid. 2006. Pembangunan Sistem Pakar pada Perangkat Mobile dengan WML dan PHP untuk Penyakit Paru pada Anak. SurabayaBroto, Adi Sadewo.2010. Perancangan dan Impelentasi Sistem Pakar untuk Analisa Penyakit Dalam. Semarang : Unversitas Diponegoro.Giarratano, J.C & Rilley G. 1994. Expert Systems: Principles and Programming, 2sd edition. USA : PWS Publishing Co.Kusrini. 2008. Aplikasi Sistem Pakar. Yogyakarta : Penerbit Andi.Martin dan Oxman dalam Kusrini. 2006. Aplikasi Sistem Pakar. Yogyakarta : Penerbit Andi.Turban, E. 1995. Decision Support System dan Expert System. USAÂ  :Prentice Hall International IncMulyono, Djoko. 2008. Pembangunan Sistem Pakar pada Perangkat Mobile dengan WML dan PHP untuk Menemukan Penyebab Kerusakan Mesin Isuzu Panther. Semarang : UnakiSurono, dkk.2009. Bahasa Indonesia Untuk Perguruan Tinggi. Semarang: Fasindo PressMc Leod dalam Turban,E. 1995. Decision Support System dan Expert System. USA : Prentice Hall International Inc.Turban dalam Mulyono, Djoko. 2008. Pembangunan Sistem Pakar pada Perangkat Mobile dengan WML dan PHP untuk Menemukan Penyebab Kerusakan Mesin Isuzu Panther. Semarang : UnakiWilson dalam Kusrini. 2006. Aplikasi Sistem Pakar. Yogyakarta : Penerbit Andi.Giarratano dan Rilley dalam Kusrini. 2006. Aplikasi Sistem Pakar. Yogyakarta : Penerbit Andi.Solichin,Achmad. 2013. Pemrograman Web dengan PHP dan MySQL. Jakarta: UBLJuman, Kundang K. 2009. Komunikasi Multimedia.JakartaNokia. 2002. XHTML Guidlines. Finlandia : Nokia Corporation.Priyandari. 2013. Tutorial Database II, Mengenal RDBMS MySQL, http://blog.priyandari.net/2013/tutorial-database-ii-mengenal-rdbms-mysql-1/, diiakses tanggal 15 Agustus 2013.Anonim. 2013. XHTML MP (eXtensible HyperText Markup Language Mobile Profile). http://www.developesrhome.com/, diakses tanggal 4 Juni 2013Dinkes Jateng. 2011. Profil Kesehatan Jateng 2011. Semarang : Dinkes JatengSetiawan (Ed). 1998. Ilmu Kebidanan, Penyakit Kandungan, dan Keluarga Berencana. Finlandia: Penerbit Buku Kedokteran EGCWiknjosastro, Hanifa. 2005. Ilmu Kandungan. Jakarta : Yayasan Bina Pustaka Sarwono Prawirohardjo.Saifuddin, Abdul Bari. 2006. Buku Acuan Nasional Pelayanan Kesehatan Maternal dan Neonatal. Jakarta : Yayasan Bina Pustaka Sarwono Prawirohardjo.Poedyasmoro, SKM. 2005. Buku Praktisi Ahli Gizi (Buku Kuliah Politeknik Kesehatan Malang). MalangWahyudi, doni. 2004. Data Mining Email. Bandung